Psychological reactions and coping strategies of Sri Lankan women carrying fetuses with lethal congenital malformations - Senanayake, H; De Silva, D; Premaratna, S; Kulatunga, M (The Sri Lanka Medical Association, 2006)
INTRODUCTION: Termination of pregnancy is a popular option for pregnancies complicated by lethal congenital malformations (LCMs). In Sri Lanka, where abortion laws are restrictive, this is not available. We studied the psychological responses and coping strategies of women who had to continue their pregnancies knowing the baby had a LCM. SETTING: A teaching hospital in Sri Lanka. STUDY DESIGN: Qualitative inquiry. METHOD: We conducted a semi-structured interview of 10 women whose fetuses were diagnosed to have a LCM. RESULTS: All women showed a grief reaction on hearing the news and were distressed about having to carry a futile pregnancy. Eight women were grateful they knew of the abnormality because it prepared them for the birth better, while the other two wished they had not known. They all found having to share facilities with 'normal' women to be painful. Seven women who received 'routine' antenatal care felt that the doctors were ill-equipped to deal with their situation. All felt that abortion should be legalised for LCMs. All engaged in religious rites believed to have miraculous powers, hoping that these will result in a normal baby. Two required specialised counselling. CONCLUSIONS: The diagnosis of a LCM causes severe distress and psychological reactions, which the staff dealing with these women should be aware of. Ideally, they should be provided care with minimum contact with other women, taking into account the futility of the pregnancy. Engagement in religious rites, even though with unreal expectations, may possibly help them in the long term bereavement process